Using Analytic Hierarchy Process (AHP) to Define the Best Programming Language for Software in Agribusiness - Lários, Gustavo Bezerra (2025)
This study develops a specialized framework for evaluating programming languages for agribusiness software development using the Analytical Hierarchy Process (AHP). The decision model was structured using the criteria Efficiency, Complexity, and Maintainability, with seven subcriteria: Execution Time, Memory Consumption, Ease of Learning, Portability, Updates, Community, and Security. The framework was validated through a comprehensive evaluation involving eight domain experts with experience in agribusiness software development. Results demonstrate that Efficiency is the most critical criterion (0.527), with Security (0.250), Ease of Learning (0.209), and Memory Consumption (0.199) being the most influential subcriteria. The analysis reveals that Python (0.397) is the preferred programming language for agribusiness applications, followed by PHP (0.264) and TypeScript/JavaScript (0.175). This research contributes to agricultural technology literature by providing a structured approach to technology selection that accounts for the specific requirements of agribusiness software development, helping developers make more informed decisions when selecting programming languages for agricultural applications.